2020
DOI: 10.1080/09168451.2020.1756213
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced lactic acid bacteria viability with yeast coincubation under acidic conditions

Abstract: The enhancing effects of yeasts on the viability of lactic acid bacteria (LAB) under acidic conditions were investigated. Meyerozyma guilliermondii, coaggregative with both LAB strains under acidic conditions, significantly enhanced the viability of Lactobacillus pentosus and L. paracasei in pH 3.0 lactic acid (LA) buffer at 10°C (p < 0.05). Non-coaggregative yeasts (Saccharomyces cerevisiae, Schizosaccharomyces pombe, and Cyberlindnera saturnus) also significantly enhanced the LAB viability (p <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…It was reported that L. plantarum in single culture fermentation lowers the pH of the medium which negatively affects the cellulase activity or stability, whereas the addition of S. cerevisiae helps to keep the pH at the optimum level required for the maximum cellulase activity and production by utilizing the metabolites produced by lactic acid bacteria Abbreviations: SCZ, stone cell group; SNZ, supernatant group; -, representatives in the corresponding group did not detect the corresponding differential metabolites. (Hirai & Kawasumi, 2020;Huang, Feng, et al, 2021;Saroj et al, 2022). S. cerevisiae also produces cellulase (Zhang et al, 2019), which enhances the overall volume of the enzyme.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that L. plantarum in single culture fermentation lowers the pH of the medium which negatively affects the cellulase activity or stability, whereas the addition of S. cerevisiae helps to keep the pH at the optimum level required for the maximum cellulase activity and production by utilizing the metabolites produced by lactic acid bacteria Abbreviations: SCZ, stone cell group; SNZ, supernatant group; -, representatives in the corresponding group did not detect the corresponding differential metabolites. (Hirai & Kawasumi, 2020;Huang, Feng, et al, 2021;Saroj et al, 2022). S. cerevisiae also produces cellulase (Zhang et al, 2019), which enhances the overall volume of the enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…A significant increase in the enzyme activity of the mixed cultures was observed probably due to metabolic or some unknown interactions between L. plantarum and the yeast. It was reported that L. plantarum in single culture fermentation lowers the pH of the medium which negatively affects the cellulase activity or stability, whereas the addition of S. cerevisiae helps to keep the pH at the optimum level required for the maximum cellulase activity and production by utilizing the metabolites produced by lactic acid bacteria (Hirai & Kawasumi, 2020; Huang, Feng, et al, 2021; Saroj et al, 2022). S. cerevisiae also produces cellulase (Zhang et al, 2019), which enhances the overall volume of the enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Widespread in nature despite their high nutritional requirements, LAB are often the natural partners of various yeasts including S. cerevisiae, forming mutually beneficial "cross-feeding"-type relationships within bacteria-yeasts communities in a variety of naturally fermented foods and beverages [15,[26][27][28]. Yeast is also known to be a natural symbiont for LAB, because the latter can reduce the pH of the medium to 3.5-4.5, which is comfortable for the yeast and detrimental to many microorganisms [14,28,29]. For example, used in this study silage-isolated strain S. bovis IMV B-7151 acidified medium to pH=4.28.…”
Section: F I G 4 the Response Surface Plots Of The Interaction Effects Of The Cultivation Parameters: (A) Starch Concentration X 1 Versusmentioning
confidence: 99%